A Preliminary Proposal for a Hybrid Lattice Confinement Fusion–Fission Reactor for Mobile Nuclear Power Plants. (19th May 2022) - Ondir Freire, Luciano; de Andrade, Delvonei Alves
Abstract: Scientists detected 2.45-MeV neutrons and in smaller yields 4- and 5-MeV neutrons in deuterated metals under a 2.9-MeV electron beam. Such discovery could allow the use of deuterated metals at temperatures below their melting point to provide nuclear fusion reactions. Such reactions could provide fast neutrons and energy in the form of heat. This work analyzed the results of some experiments to infer the neutron multiplication rate in such environments. It also considered the possible roles that such phenomena could play in a commercial nuclear power reactor under economic and compactness constraints. It seems the best way to promote nuclear fusion is the irradiation of deuterated metals by fast neutrons. This work presents the concept of a hybrid fusion–fission reactor using fissile or fertile fuel to generate heat and fast neutrons along deuterated metals providing excess neutrons (reactivity boost). Additionally, deuterated metals also may have a role in neutron moderation requiring less volume than other moderators (water or graphite). Such a reactor, given its reactivity boost, may burn radioactive residuals (transmutation) at affordable costs while generating power. Alternatively, this hybrid fusion–fission concept could also breed fissile fuel from fertile isotopes using natural uranium as seed.